IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA BAMBAIRA KECAMATAN BAMBAIRA KABUPATEN PASANGKAYU - Muh. Nasir; Nuraisyah Nuraisyah; Dandan Haryono (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
Implementation of the Village Fund Allocation Policy in Bambaira Village, Sarjo District, Pasang Kayu Regency. The research method uses a qualitative descriptive approach and determines informants purposively. The research informants were the Head of Bambaira Village, BPD of Bambaira Village, Village Secretary of Bambaira Village, Finance Staff and Planning Head of Bambaira Village. Data collection uses observation, interviews and documentation. Data analysis uses Miles and Huberman's interactive model approach, namely data collection, data reduction, data presentation, and conclusion verification. The research results show that: (1) Policy standards and targets are less effective, such as the village development program implemented by the Bambaira village government through village meetings which is still not on target, giving rise to dynamics or differences in perception between the village government and the BPD in formulating village development programs. (2) Educational resources for implementing Village Fund Allocation in Bambaira Village are still low, thus affecting the quality of work and resources to support facilities for use. Then, in realizing the village fund allocation policy, cooperation is needed, but this has not gone well so matters related to village development still need to be discussed openly, both in formal and non-formal activities.